Integrated versus non-integrated perspectives of auditors concerning the new ISO 9001 revision - Domingues, J. P. T. (2016)
The process of integration of management systems is being unfolded by a great deal of companies nowadays. A crucial feature of it relates with the audit function and the integrated perceptions of the auditors. This issue is of utmost importance if one takes into account the remarkable effort developed by ISO in the last revisions (2015) of the ISO 9001 and ISO 14001 standards aiming at the standards integration by adopting a common high level structure, identical core context, and common terms and common definitions. The available drafts of the new ISO 45001 standard suggest the same effort. This paper aims, within a global research study on ISO 9001:2015, to report the integrated versus non-integrated perspectives of auditors concerning the new ISO 9001 revision based on the results from a survey conducted among IRCA auditors. It is intended specifically to assess if the perceptions from the auditors holding several certifications are different of those from the auditors that hold solely the QMS certification. Results suggest that the auditors holding several certifications foreseen more benefits from this new revision, i.e., auditors with a wider integrated perspective rate systematically higher the different dimensions assessed in this survey.